An Embryonic Zebrafish Model to Screen Disruption of Gut-Vascular Barrier upon Exposure to Ambient Ultrafine Particles - Kyung In Baek; Yi Qian; Chih-Chiang Chang; Ryan O’Donnell; Ehsan Soleimanian; Constantinos Sioutas; Rongsong Li; Tzung K. Hsiai (Toxics, 2020)
Epidemiological studies have linked exposure to ambient particulate matter (PM) with gastrointestinal (GI) diseases. Ambient ultrafine particles (UFP) are the redox-active sub-fraction of PM2.5, harboring elemental and polycyclic aromatic hydrocarbons from urban environmental sources including diesel and gasoline exhausts. The gut-vascular barrier (GVB) regulates paracellular trafficking and systemic dissemination of ingested microbes and toxins. Here, we posit that acute UFP ingestion disrupts the integrity of the intestinal barrier by modulating intestinal Notch activation. Using zebrafish embryos, we performed micro-gavage with the fluorescein isothiocynate (FITC)-conjugated dextran (FD10, 10 kDa) to assess the disruption of GVB integrity upon UFP exposure. Following micro-gavage, FD10 retained in the embryonic GI system, migrated through the cloaca. Conversely, co-gavaging UFP increased transmigration of FD10 across the intestinal barrier, and FD10 fluorescence occurred in the venous capillary plexus. Ingestion of UFP further impaired the mid-intestine morphology. We performed micro-angiogram of FD10 to corroborate acute UFP-mediated disruption of GVB. Transient genetic and pharmacologic manipulations of global Notch activity suggested Notch regulation of the GVB. Overall, our integration of a genetically tractable embryonic zebrafish and micro-gavage technique provided epigenetic insights underlying ambient UFP ingestion disrupts the GVB.